188k views
4 votes
Write an explicit rule for the recursive rule. a1=−2,an=9an−1

User Eluong
by
5.8k points

1 Answer

4 votes

Answer:


a_n=-2\cdot 9^(n-1).

Explanation:

You are given that


  • a_1=-2;

  • a_n=9a_(n-1).

Then


a_1=-2,\\ \\a_2=9a_1=9\cdot (-2)=-18,\\ \\a_3=9a_2=9\cdot (-18)=-162, \dots

Actually, this sequence is the geometric seequence with first term
a_1=-2 and ratio
r=9.

The explicit rule for the nth term of the geometric sequence is


a_n=a_1\cdot r^(n-1).

Hence,


a_n=-2\cdot 9^(n-1).

User Francis Bartkowiak
by
5.7k points